THE INFLUENCE OF FAMILY-BASED SURVEILLANCE METHODS ON THE DISCOVERY OF SUSPECTED PULMONARY TUBERCULOSIS IN PADANG PARIAMAN DISTRICTS IN 2017 - Destri Suari; Nursal Asbiran; Sukarsi Rusti (Universitas Fort De Kock, 2021)
The discovery of suspect is one effort to cope with pulmonary tuberculosis. Active findings that have been done such as home visits, empowerment of cadres, and counseling has not been maximized. The problem in this study is whether the influence of family-based surveillance method to the discovery of suspect tuberculosis lung in padang pariaman district in 2017. This study aims to see the picture and the influence of independent variables on the dependent variable in Padang Pariaman district in 2017.This type of research is quantitative with pre experimental design research design conducted in December 2017 until the month of Januari 2018. The sample in this study is the head of the family in the village Pungguang Kasiak which amounted to 50 families head . The results of this study indicate that family-based surveillance methods have an effect on the discovery of suspected pulmonary tuberculosis because there is a difference between the number of suspects before and after family-based surveillance methods (mean = - 0,380). Therefore, the family is expected to play a more active role, and can be more concerned about the health of themselves and family members so that if you experience symptoms of pulmonary tuberculosis immediately checked into health services